2011
DOI: 10.1103/physrevb.84.214516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of charge inhomogeneities on elementary excitations inLa2xSrxCuO4

Abstract: Purely local experimental probes of many copper oxide superconductors show that their electronic states are inhomogeneous in real space. For example, scanning tunneling spectroscopic (STS) imaging shows strong variations in real space, and according to nuclear quadrupole resonance (NQR) studies the charge distribution in the bulk varies on the nanoscale. However, the analysis of the experimental results utilizing spatially-averaged probes often ignores this fact. We have performed a detailed investigation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…[50] These experiments and related calculations are extensively covered in the previous review by L. Pintschovius. [10] A recent investigation of Park et al [51] also revealed that the linewidth of the zone boundary bond-stretching phonon (around q=(0.5,0,0)) broadens strongly when the doping, x, is reduced and then narrows abruptly at x=0. They explained this effect in light of NQR/NMR results showing that the doped carrier concentration in the Cu-O planes is inhomogeneous, and since the zone boundary phonon frequency depends on doping, the experimental lineshape broadens.…”
Section: Lessons Learned From Model Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…[50] These experiments and related calculations are extensively covered in the previous review by L. Pintschovius. [10] A recent investigation of Park et al [51] also revealed that the linewidth of the zone boundary bond-stretching phonon (around q=(0.5,0,0)) broadens strongly when the doping, x, is reduced and then narrows abruptly at x=0. They explained this effect in light of NQR/NMR results showing that the doped carrier concentration in the Cu-O planes is inhomogeneous, and since the zone boundary phonon frequency depends on doping, the experimental lineshape broadens.…”
Section: Lessons Learned From Model Systemsmentioning
confidence: 95%
“…Note that the enhancement of the linewidth at x=0.07 near the zone boundary compared with the higher dopings is unrelated to the anomaly at h=0.3 and can be explained by the inhomogeneous doping effect discussed in sec. 4.1 and[51].…”
mentioning
confidence: 99%
“…It was shown in Ref. 20 that this effect originates from inhomogeneous doping combined with doping-induced phonon softening at Sr concentrations below optimal doping. Since the dopingdependence of the phonon frequency increases towards the zone boundary, the width of the measured phonon spectrum increases smoothly towards the zone boundary as well.…”
mentioning
confidence: 99%
“…However phonon-phonon coupling (anharmonicity) also broadens the phonon peaks and electron-electron interactions can broaden the electronic quasiparticles. Disorder can further increase the linewidths [13], so extracting electron-phonon coupling strength from the linewidths of quasiparticle peaks is challenging.…”
mentioning
confidence: 99%